PROGRAM KLASIFIKASI MANAJEMEN LABA PADA BANK SYARIAH MENGGUNAKAN LOGIKA FUZZY BERBASIS MATLAB - Putri, Rizka Yulianti; Agushinta R, Dewi; Octavia, Martina; Ediraras, Dharma Tintri (Computatio : Journal of Computer Science and Information Systems, 2019)
Earnings management behavior is management's intervention in the financial accounting process to produce financial reports to external parties in order to achieve a certain profit level, which aims to benefit himself or the entity. A Fuzzy method is a system built with definitions, ways of working, and clear descriptions based on Fuzzy logic theory and has several processes such as Fuzzy rules, inference, fuzzification, defuzzification. A Fuzzy method can handle the obscurity, uncertainty of the variables used and can map an input space into the output space using Fuzzy rules. Earnings management is defined as the efforts of company managers to intervene or influence the information in financial statements to trick stakeholders who want to know the performance and condition of the company. A program to classify several Sharia banks in Indonesia and Malaysia is made to find out and compare whether the Sharia banks do earnings management. The input used is the calculation result of the average Islamic bank earnings management that has been normalized, while the output is the classification of bank earningsmanagement. Fuzzy Inference uses the Mamdani method. The forming process of this Fuzzy model requires MATLAB R2017a software Perilaku manajemen laba atau earning management adalah campur tangan manajemen dalam proses akuntansi keuangan untuk menghasilkan laporan keuangan kepada pihak eksternal guna mencapai tingkat laba tertentu, yang bertujuan untuk menguntungkan dirinya sendiri atau entitas. Metode Fuzzy adalah suatu sistem yang dibangun dengan definisi, cara kerja, dan deskripsi yang jelas berdasarkan teori logika Fuzzy dan memiliki beberapa proses seperti aturan Fuzzy, inferensi, fuzzifikasi, deffuzifikasi. Studi ini bertujuan untuk mengklasifikasikan bentuk praktek manajemen laba pada bank Syariah di Indonesia dan Malaysia (ASEAN) dibuat untuk mengetahui dan membandingkan polla praktek manajemen laba. Input yang digunakan dalam penelitian ini adalah hasil perhitungan rata-rata manajemen laba bank Syariah yang telah dinormalisasi, sedangkan output pada penelitian ini adalah klasifikasi manajemen laba bank tersebut. Inferensi Fuzzy yang digunakan adalah metode Mamdani. Proses pembentukan model Fuzzy dibuat dengan software MATLAB R2017a.